REVOLTING EFFECTS IN OWN ROTATION OF HIGH-ORBITAL SATELLITES - Epishev, V. P.; Isak, I. I.; Motrunich, Y. M.; Motrunich, I. I.; Naubauer, I. F.; Pop, S. S.; Kudak, V. I. (Одеські астрономічні публікації, 2017)
Character of own satellites rotation is analysed, depending on the height of their flight. Results of determination of size of indignations which have influence on a rotation of the probed objects are brought. On the basis of the got results the attempt of estimation of relative change of sun permanent on solar period is done.